A flexible high-performance oxygen evolution electrode with three-dimensional NiCo2O4 core-shell nanowires. (January 2015) - Chen, Rong; Wang, Hsin-Yi; Miao, Jianwei; Yang, Hongbin; Liu, Bin
Abstract: Three-dimensional NiCo2 O4 core-shell nanowires made up of NiCo2 O4 nanowire core and NiCo2 O4 nanoflake shell have been fabricated by a simple two-step wet chemical method on flexible conductive carbon cloth substrate for oxygen evolution reaction (OER). The combination of high surface area, enhanced mass and charge transport as well as three-dimensional conducting pathway enables superior oxygen evolution reaction. Notably, the NiCo2 O4 core-shell nanowire electrode exhibits large anodic current and low onset overpotential for OER with an overpotential of 320 mV at a current density of 10 mA/cm 2 . Furthermore, the NiCo2 O4 core-shell nanowire electrode possesses excellent electrocatalytic stability with long hour electrolysis showing no visible degradation, which is highly desirable for a promising OER electrocatalyst. Graphical abstract: